{[xˆ(-2)+yˆ(-2)]/[xˆ(-2/3)+yˆ(-2/3)]}-{[xˆ(-2)-yˆ(-2)]/xˆ(-2/3)-yˆ(-2/3)}

来源:学生作业帮助网 编辑:作业帮 时间:2021/06/25 17:52:38

{[xˆ(-2)+yˆ(-2)]/[xˆ(-2/3)+yˆ(-2/3)]}-{[xˆ(-2)-yˆ(-2)]/xˆ(-2/3)-yˆ(-2/3)}
{[xˆ(-2)+yˆ(-2)]/[xˆ(-2/3)+yˆ(-2/3)]}-{[xˆ(-2)-yˆ(-2)]/xˆ(-2/3)-yˆ(-2/3)}

{[xˆ(-2)+yˆ(-2)]/[xˆ(-2/3)+yˆ(-2/3)]}-{[xˆ(-2)-yˆ(-2)]/xˆ(-2/3)-yˆ(-2/3)}
原式=[x^﹙-2/3﹚+y^﹙-2/3﹚][(x^﹙﹣4/3﹚-x^﹙﹣2/3﹚y^﹙-2/3﹚+y^﹙-4/3)] /
(x^﹙﹣2/3﹚+y^﹙-2/3)-[x^﹙﹣2/3﹚-y^﹙-2/3)][(x^﹙﹣4/3﹚+x^﹙﹣2/3﹚y^﹙-2/3﹚+y^﹙-4/3) ]/[x^﹙﹣2/3﹚-y^﹙-2/3)]
=x^﹙﹣4/3﹚-x^﹙﹣2/3﹚y^﹙-2/3﹚+y^﹙-4/3﹚-x^﹙﹣4/3﹚-x^﹙﹣2/3﹚y^﹙-2/3﹚-y^﹙-4/3﹚
=﹣2x^﹙﹣2/3﹚y^﹙-2/3﹚

我看不清呀

分子是立方和和立方差

原式=(x^2/3+y^-2/3)(x^4/3-x^2/3y^-2/3+y^-4/3) /(x^2/3+y^-2/3)-(x^2/3-y^-2/3)(x^4/3+x^2/3y^-2/3+y^-4/3) /(x^2/3-y^-2/3)
=x^4/3-x^2/3y^-2/3+y^-4/3-x^4/3-x^2/3y^-2/3-y^-4/3
=-2x^2/3y^-2/3